Perancangan Animasi 3D Teknik Dasar Taekwondo Menggunakan Unity - Mufti, Fachri; Khairunnisa, Khairunnisa (Universitas Harapan Medan, 2024)
Many criminal acts often happen to everyone, such as sexual violence, pickpocketing, and others. Therefore, everyone must also be able to protect themselves from violence that can occur anywhere and also protect themselves from cities affected by crime. In Indonesia, there are generally martial arts such as karate, pencak silat, and others. In this study, we will explain the basic techniques of taekwondo martial arts. This learning uses an animated video tutorial of one of the knowledge used as access to the learning process. In learning the animation of basic taekwondo martial techniques, everyone must have an animation video of the basic taekwondo techniques. This animated video uses Unity software.